Recombinant Uncarboxylated Osteocalcin Per Se Enhances Mouse Skeletal Muscle Glucose Uptake in both Extensor Digitorum Longus and Soleus Muscles - Lin, Xuzhu; Parker, Lewan; Mclennan, Emma; Zhang, Xinmei; Hayes, Alan; McConell, Glenn; Brennan-Speranza, Tara C.; Levinger, Itamar (Frontiers in Endocrinology, 2017)
Emerging evidence suggests that undercarboxylated osteocalcin (ucOC) improves muscle glucose uptake in rodents. However, whether ucOC can directly increase glucose uptake in both glycolytic and oxidative muscles and the possible mechanisms of action still need further exploration. We tested the hypothesis that ucOC per se stimulates muscle glucose uptake via extracellular signal-regulated kinase (ERK), adenosine monophosphate-activated protein kinase (AMPK), and/or the mechanistic target of rapamycin complex 2 (mTORC2)-Protein Kinase B (AKT)-AKT substrate of 160 kDa (AS160) signaling cascade. Extensor digitorum longus (EDL) and soleus muscles from male C57BL/6 mice were isolated, divided into halves and then incubated with ucOC with or without the pretreatment of ERK inhibitor U0126. ucOC increased muscle glucose uptake in both EDL and soleus. It also enhanced phosphorylation of ERK2 (Thr202/Tyr204) and AS160 (Thr642) in both muscle types, and increased mTOR phosphorylation (Ser2481) in EDL only. ucOC had no significant effect on the phosphorylation of AMPK (Thr172). The inhibition of ucOC-induced ERK phosphorylation had limited effect on ucOC-stimulated glucose uptake and AS160 phosphorylation in both muscle types, but appeared to inhibit the elevation in AKT phosphorylation only in EDL. Taken together, ucOC at the physiological range directly increased glucose uptake in both EDL and soleus muscles in mouse. The molecular mechanisms behind this ucOC effect on muscle glucose uptake seem to be muscle type-specific, involving enhanced phosphorylation of AS160 but limitedly modulated by ERK phosphorylation. Our study suggests that, since ucOC increases muscle glucose uptake without insulin, it could be considered as a potential agent to improve muscle glucose uptake in insulin resistant conditions.